Exploring the feasibility of theory synthesis: A worked example in the field of health related risk-taking. (January 2015) - Pound, Pandora; Campbell, Rona
Abstract: The idea of synthesising theory is receiving attention within public health as part of a drive to design theoretically informed interventions. Theory synthesis is not a new idea, however, having been debated by sociologists for several decades. We consider the various methodological approaches to theory synthesis and test the feasibility of one such approach by synthesising a small number of sociological theories relevant to health related risk-taking. The synthesis consisted of three stages: (i) synthesis preparation, wherein parts of relevant theories were extracted and summarised; (ii) synthesis which involved comparing theories for points of convergence and divergence and bringing together those points that converge; and (iii) synthesis refinement whereby the synthesis was interrogated for further theoretical insights. Our synthesis suggests that serious and sustained risk-taking is associated with social isolation, liminality and a person's position in relation to the dominant social group. We reflect upon the methodological and philosophical issues raised by the practice of theory synthesis, concluding that it has the potential to reinvigorate theory and make it more robust and accessible for practical application. Highlights: There is increasing discussion of synthesising theory within public health. We conducted a synthesis of theories of risk-taking, to test the method. The synthesis revealed serious risk-taking to be associated with liminality. Synthesis is feasible and makes theory more accessible for practical application. The process of synthesising theory raises philosophical issues, which we discuss.